Clusters and case vignettes of impaired maternal–fetal bonding in pregnancy: A mixed method approach - Toshinori Kitamura; Ayako Hada; Yuriko Usui; Yukiko Ohashi (PCN Reports)
Abstract Aim Clinical attention to and understanding of women with impaired fetal bonding is important for early therapeutic intervention. This study aimed to clarify the clinical characteristics of women belonging to groups derived by cluster analysis of impaired maternal–fetal bonding. Methods A mixed‐method approach was adopted. We conducted a two‐wave internet survey targeting pregnant women less than 36 gestational weeks by using a questionnaire (33‐item Dimensional Assessment of Mother Baby Organization Questionnaire [DAMBO Q33]) with subsequent online interviews (Dimensional Assessment of Mother and Baby Organization‐Research Version). The maternal–fetal bonding disorder items in the DAMBO Q33 were entered into a two‐step cluster analysis. Two representative cases from each of the clusters, except for the positive bonding cluster, were selected to describe their clinical pictures. Finally, quantitative data and qualitative data were integrated and interpreted. Results A two‐step cluster analysis elicited four clusters: bonding disorder (n = 101), ambivalent bonding (n = 156), positive bonding (n = 173), and lack of bonding emotions (n = 122). Women in the bonding disorder cluster were characterized by seriously negative feelings towards the fetus. Women in the ambivalent bonding cluster wished to be pregnant but were not sufficiently ready for the transition into parenthood. Women in the lack of bonding emotions cluster were characterized by a lack of strong interest in pregnancy and the fetus. Conclusion Patterns of impaired maternal–fetal bonding were identified. We should not think of a pathological category of mental illness among them but recognize that such parents are targets for professional assessments and supportive (therapeutic) interventions. Understanding the meaning of getting pregnant and difficulties in the process of maternal role attainment is required.